Longitudinal low density lipoprotein cholesterol goal achievement and cardiovascular outcomes among adult patients with familial hypercholesterolemia: The CASCADE FH registry. (October 2019) - Duell, P. Barton; Gidding, Samuel S.; Andersen, Rolf L.; Knickelbine, Thomas; Anderson, Lars; Gianos, Eugenia; Shrader, Peter; Kindt, Iris; O'Brien, Emily C.; McCann, Dervilla; Hemphill, Linda C.; Ahmed, Catherine D.; et al.
Abstract: Background and aims: There are limited data from the US on outcomes of patients in specialty care for familial hypercholesterolemia (FH). Methods: CASCADE FH Registry data were analyzed to assess longitudinal changes in medication usage, in low density lipoprotein cholesterol (LDL-C) levels, and the rate of major adverse cardiovascular events (MACE (myocardial infarction, coronary revascularization, stroke or transient ischemic attack) in adults with FH followed in US specialty clinics. Results: The cohort consisted of 1900 individuals (61% women, 87% Caucasian), with mean age of 56 ± 15 years, 37% prevalence of ASCVD at enrollment, mean pretreatment LDL-C 249 ± 68 mg/dl, mean enrollment LDL-C 145 mg/dl and 93% taking lipid lowering therapy. Over follow up of 20 ± 11 months, lipid lowering therapy use increased (mean decrease in LDL-C of 32 mg/dl ( p < 0.001)). Only 48% of participants achieved LDL-C < 100 mg/dl and 22% achieved LDL-C < 70 mg/dl; ASCVD at enrollment was associated with greater likelihood of goal achievement. MACE event rates were almost 6 times higher among patients with prior ASCVD compared to those without (4.6 vs 0.8/100 patient years). Also associated with incident MACE were markers of FH severity and conventional ASCVD risk factors. Conclusions: With care in FH specialized clinics, LDL-C decreased, but LDL-C persisted >100 mg/dl in 52% of patients. High ASCVD event rates suggest that adults with FH warrant designation as having an ASCVD risk equivalent. Earlier and more aggressive therapy of FH is needed to prevent ASCVD events. Graphical abstract: Image 1 Highlights: Adults with familial hypercholesterolemia in lipid specialty clinics achieve further LDL-C lowering in specialty care but less than half get to LDL-c < 100 mg/dl. Atherosclerotic event rates remain high, including among those with prior atherosclerotic vascular disease and average LDL-c < 100 mg/dl.